Психологическая поддержка воспитателей, работающих с детьми с ограниченными возможностями здоровья в условиях инклюзивного образования (SCIENCE and SOCIETY, 2025)
The article addresses the need for systematic psychological support for preschool teachers working in inclusive education settings with children with disabilities. The article concludes that institutionalizing systemic psychological support is essential to ensuring the quality of inclusive preschool education.